Beyond Technocracy Science, Politics and Citizens - Bucchi, Massimiano (Springer New York : Imprint: Springer, 2009)
Nuclear energy, stem cell technology, GMOs: the more science advances, the more society seems to resist. But are we really watching a death struggle between opposing forces, as so many would have it? Can today's complex technical policy decisions coincide with the needs of a participatory democracy? Are the two sides even equipped to talk to each other? Beyond Technocracy: Science, Politics and Citizens answers these questions with clarity and vision. Drawing upon a broad range of data and events from the United States and Europe, and noting the blurring of the expert/lay divide in the knowledge base, the book argues that these conflicts should not be dismissed as episodic, or the outbursts of irrationality and ignorance, but recognized as a critical opportunity to discuss the future in which we want to live. Massimiano Bucchi's analysis covers the complex realities of post-academic science as he: Explores the widely debated theme of science and democracy across a broad range of technological controversies. Overviews issues raised by the current relationship among scientists, policymakers, business interests, and the public. Dispels stereotypes of the detached scientific community versus the uninformed general public. Examines the role of the media in framing scientific debate. Addresses the question of how to move beyond technocracy to a more fruitful collaboration between scientists and citizens. Offers a bold vision for a future in which the scientific and public spheres regard each other as partners working toward a shared purpose. Beyond Technocracy: Science, Politics and Citizens has great value as a postgraduate text for courses in technology and society, political science, and science policy. It will also find an interested audience among scientists, policymakers, managers in the technological sector, and concerned lay readers. Praise for Beyond Technocracy "Bucchi provides a clear, rigorous and accessible discussion - often enriched by a subtle irony - of complex and ambiguous issues, showing that science and innovation are not neutral terrains, but rather among the key conflictual contexts in which contemporary social and political changes take place." -Italian Review of Sociology "In his brilliant new book, Beyond Technocracy: Science, Politics and Citizens, Massimiano Bucchi opens for the reader the Pandora's box of the complex relationship between scientists and citizens in contemporary, democratic societies...Based on a wealth of empirical evidence and case studies, the book is extremely accessible and well written, making it an ideal introduction to the issues. I would highly recommend it to specialists and non-specialists alike!" -Professor Roberto Franzosi, Emory University "A dense but accessible book...Bucchi acutely describes the shortcomings of the technocratic and ethical responses to the contemporary dilemmas of science and technology." -Italian Edition of the New York Review of Books .